Improving Students’ Creative Thinking Skills by Combining Cooperative Script and Reciprocal Teaching Models - Ali Usman; Novy Eurika; Ika Priantari; Ahmad Rusdy Awalludin; Gumilang Mutiara Hilia (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to describe the increase in students' creative thinking by combining cooperative script learning models with reciprocal teaching. This research is a Class Action Research (CAR). This research was conducted in class XI SMA. Learning tools, essay questions combined with creative thinking, observation sheets of learning implementation, and creative thinking instruments were used to collect data. Data analysis on the increase in creative thinking was calculated using the score gain (N-Gain) formula. The results show an increase in students' creative thinking, namely from cycle I with a score of 0.28 which is included in the low category, rising to a score of 0.5 in cycle II which is included in the medium category. The results of this study indicate an increase in students' learning activities and creative thinking in each learning cycle. Combining cooperative and reciprocal learning models can encourage students to dare to express opinions, thoughts, and ideas to empower students' creative thinking skills. This shows that applying the cooperative learning model, a combination of collaborative learning models with a reciprocal teaching model used continuously, can increase students' learning activities and creative thinking to train them to become self-regulation learners.